Surgical Training in Resource-Limited Settings: Cost-Effective, Portable and Reproducible Personal Laparoscopic Endotrainer - Shrestha, Sujan; KC, Ajay; Shrestha, Shiba (Journal of Institute of Medicine Nepal, 2023)
Introduction Minimal invasive surgery (MIS) is standard of approach for many surgical pathologies. The best way to enhance the psychomotor skills for MIS is through the disciplined and structured time with the Endotrainer. The cost and portability of available Endotrainer is the main reason for surgeons and residents allocating minimal time for training. Our goal was to create cost-effective and portable Endotrainer that enables skill development at home and classroom setting. Methods The framework of this Endotrainer was made-up of local plywood. The anterior surface was divided into nearly equal superior and inferior surface by horizontal plywood stick. A rectangular window was created at the anterior surface for mobile phone or tablet or iPad placement. Similarly, two 8 mm hole were drilled and padded with locally available rubber washer inferior and lateral to rectangular window as laparoscopic ports. For light commercially available mini dimmable LED was installed. The final trainer box was similar in shape and size of medium suitcase, which was portable and could house laparoscopic hand instruments and training pads. Conclusion The Endotrainer was easy and cost-effective to assemble. Embodying the essence of portability and reproducibility, this trainer box offers a personal practice tool that empowers trainee to sharpen their skills at their home or classroom.